Shame, face and social relations in Northern China: ramifications for social assistance provision - Yang, L; Walker, R; Xie, J (Cambridge University Press, 2019)
While it is increasingly recognized that shame is a pernicious component of the experience of poverty, the stigma generally associated with social assistance provision is less marked with respect to China's Minimum Living Security System, also known as dibao. This enigma is explored and illuminated drawing on two streams of indigenous Chinese scholarship and qualitative fieldwork in eight villages in Shanxi province. Economic and political changes prioritizing economic growth and individual wealth have increased the shame associated with poverty, manifest as loss of face, low mian (status) and lack of lian (integrity). However, this shame does not transfer to dibao because the scheme has been transformed locally into a universal age supplement that partially fulfils the demands of filial piety and which is seen to reflect and contribute to guanxi (social influence).